Role of Extractives in the Development of Bond Strength - Gupta, R. C.; Jain, D. K. (Indian Forester, 1980)
Five common Indian species which are used for plywood making were selected to study the role of extractives in the rate of development of bond strength using cold set Urea-formaldehyde resin as glue. Extraction with hot water decreased the failing load from that of control (unextracted) values while extraction with ether, alcohol/benzene improved the bonding strength. Rate of development of bond strength is only slightly effected with the type of extraction carried out and it is maximum in case of ether, alcohol/benzene extraction in most of the cases.